2006
DOI: 10.1073/pnas.0600220103
|View full text |Cite
|
Sign up to set email alerts
|

Long-range cooperative binding effects in a T cell receptor variable domain

Abstract: Although cellular processes depend on protein-protein interactions, our understanding of molecular recognition between proteins remains far from comprehensive. Protein-protein interfaces are structural and energetic mosaics in which a subset of interfacial residues, called hot spots, contributes disproportionately to the affinity of the complex. These hot-spot residues can be further clustered into hot regions. It has been proposed that binding energetics between residues within a hot region are cooperative, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(84 citation statements)
references
References 43 publications
2
82
0
Order By: Relevance
“…Such communication between distant sites in proteins has been observed in many systems (33,34), and it appears to involve long range perturbations in electrostatic fields or vibrational modes that are still poorly understood.…”
Section: Structure Of the Ly49c-h-2k Bmentioning
confidence: 99%
“…Such communication between distant sites in proteins has been observed in many systems (33,34), and it appears to involve long range perturbations in electrostatic fields or vibrational modes that are still poorly understood.…”
Section: Structure Of the Ly49c-h-2k Bmentioning
confidence: 99%
“…No contacts with residues from the CDR1, CDR3 or HV4 loops are made with TSST-1. Hot spot residues located from the CDR2 and FR3 on opposite sides of the binding interface act synergistically to bind TSST-1 in an energetically cooperative manner [38].…”
Section: Bacterial Superantigens Can Be Grouped Evolutionarilymentioning
confidence: 99%
“…Binding to the TCR Vβ CDR2 loop is a requirement for all bacterial SAGs, and the proportion of the SAG-TCR interface that is contributed by the CDR2 loop is invariably the greatest in any SAG-TCR complex, relative to any other single hypervariable or framework region. Involvement of Vβ domain regions beyond the CDR2 loop, however, plays a significant role in the TCR Vβ domain specificity and cross-reactivity of a SAG [38,49,54]. SEK and TSST-1 engage one or more framework region apical loops, at the expense of contacting the hypervariable elements.…”
Section: Sag-tcr Specificity and Cross-reactivitymentioning
confidence: 99%
“…Alanine scanning analysis has revealed that some binding hot spots are conserved within protein families [19], whereas others are specific to each family member [20][21][22]. Experiments have emphasized the modular design of binding sites, with energetic cooperative contribution of single residues within the module; and additive between modules [23][24][25]. Computational protein design methods have also been used to elucidate the tradeoff between stability and specificity for the optimization of biological function [8,26].…”
Section: Introductionmentioning
confidence: 99%